2022
DOI: 10.3389/fcimb.2022.937039
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Oral Condition Analysis and the Influence of Highly Active Antiretroviral Therapy on Human Salivary Microbial Community Diversity in HIV-Infected/AIDS Patients

Abstract: The purpose of this study was to assess the clinical oral status and investigate the effect of highly active antiretroviral therapy (HAART) on oral flora diversity in human immunodeficiency virus (HIV)-infected/acquired immune deficiency syndrome (AIDS) patients. We first recorded and analyzed the demographic indicators of 108 HIV-infected patients and assessed their periodontal health, dental health and oral lesion status by oral examination. Besides, we compared the changes in salivary microbial communities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Non-adherent ART for a long time results in the patient's immunosuppressed condition which results in more frequent or more severe OI, and can be the cause of serious morbidity and even mortality (Duff, 2019). Preventing OI can be initiated by vaccination, such as meningococcal infection, pneumococcal infection, hepatitis A and B, influenza and varicella, but it is not the most effective solution (Cao et al, 2022). Other major OI requires prophylactic antibiotics or antiviral medications (Sangeda et al, 2018), so it is very important for them to increase ART.…”
Section: Discussionmentioning
confidence: 99%
“…Non-adherent ART for a long time results in the patient's immunosuppressed condition which results in more frequent or more severe OI, and can be the cause of serious morbidity and even mortality (Duff, 2019). Preventing OI can be initiated by vaccination, such as meningococcal infection, pneumococcal infection, hepatitis A and B, influenza and varicella, but it is not the most effective solution (Cao et al, 2022). Other major OI requires prophylactic antibiotics or antiviral medications (Sangeda et al, 2018), so it is very important for them to increase ART.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the impact of HIV-infection in the bacterial diversity of oral microbiota, conflicting results are found in the literature: while a few studies showed no significant difference between PLWH and controls ( Mukherjee et al., 2014 ; Goldberg et al., 2015 ; Gonçalves et al., 2019 ; Meng et al., 2023 ), other studies found significant differences between both groups ( Gonçalves et al., 2007 ; Silva-Boghossian et al., 2008 ; Iwai et al., 2012 ; Hegde et al., 2014 ; Li et al., 2014 ; Kistler et al., 2015 ; Noguera-Julian et al., 2017 ; Presti et al., 2018 ; Griffen et al., 2019 ; Lewy et al., 2019 ; Coker et al., 2020 ; Yang et al., 2020 ; Perez Rosero et al., 2021 ; Guo et al., 2021b ; Cao et al., 2022 ; Ramos Peña et al., 2022 ; Beall et al., 2023 ; Kuhn et al., 2023 ).…”
Section: Assessment Of the Oral Microbiomementioning
confidence: 99%
“…The reported results regarding bacterial taxonomy in PLWH differed according to the type of samples, being saliva, biofilm, oral rinses and mucosal swabs, the most common methods used to assess the oral microbiota. The main taxonomical differences found in PLWH have been related to increased abundance of genera such as Campylobacter , Granulicatella, Neisseria , Fusobacterium , and Selenomonas ( Li et al., 2014 , 2021 ; Guo et al., 2021b ; Cao et al., 2022 ), and decreased abundance of Actinomyces, Lactobacillus, Peptostreptococcus and Treponema ( Gonçalves et al., 2007 ; Silva-Boghossian et al., 2008 ; Annavajhala et al., 2020 ; Ramos Peña et al., 2022 ). On the other hand, an association with increased abundance of Lactobacillus , Lautropia and Bacteroides has been reported in controls ( Li et al., 2014 ; Imahashi et al., 2021 ; Li et al., 2021 ) ( Table 2 and Figure 1 ).…”
Section: Assessment Of the Oral Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies among PLWH have found an association between increased severity of periodontitis and increased prevalence of P. gingivalis, elevated C-reactive protein (CRP) levels, and higher proportions of circulating CD8 + cells [10]. Other studies suggest that ART may have an important role in balancing the salivary microecological oral environment [11]. Consequently, this study seeks to assess alveolar bone loss, gingival crevicular uid cytokine markers, and periodontal disease activity in men.…”
Section: Introductionmentioning
confidence: 99%